Riemann's Zeta Function - Edwards,H.M (Newyork : Dover, 1974)
Superb study of one of the most influential classics in mathematics examines the landmark 1859 publication entitled "On the Number of Primes Less Than a Given Magnitude," and traces developments in theory inspired by it. Topics include Riemann's main formula, the prime number theorem, the Riemann-Siegel formula, large-scale computations, Fourier analysis, and other related topics.
Keywords: Number theory; Riemann hypothesis